2014
DOI: 10.1155/2014/427062
|View full text |Cite
|
Sign up to set email alerts
|

The Work behind Weight-Loss Surgery: A Qualitative Analysis of Food Intake after the First Two Years Post-Op

Abstract: Purpose. Obesity has reached epidemic proportions in the U.S. and has nearly doubled worldwide since 1980. Bariatric surgery is on the rise, but little focus has been placed on the psychosocial impacts of surgery. The purpose of this study was to explore experiences of patients who have undergone bariatric surgery at least two years before to gain an understanding of the successes and challenges they have faced since surgery. Methods. This study used a phenomenological approach, to investigate the meaning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 16 publications
1
27
0
6
Order By: Relevance
“…Routine appointments and monitoring motivated some people to attend , but others reported difficultly attending due to location , time of appointment , work or family commitments or expense . Some had an expectation that the HCPs would initiate more contact .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine appointments and monitoring motivated some people to attend , but others reported difficultly attending due to location , time of appointment , work or family commitments or expense . Some had an expectation that the HCPs would initiate more contact .…”
Section: Resultsmentioning
confidence: 99%
“…Many patients recognized their need for help from psychologists (41)(42)(43)(44)54), valued it (53) and desired greater access to psychological support (31,(41)(42)(43)(44)(45)(46)(47)(48)(51)(52)(53)(54)(55). Access to support groups was valued (43,49), but others perceived them as offering care mainly for those in the immediate post-op period with longer term patients feeling 'alienated by the topics and discussions' (52). In addition, although keen to attend support groups, patients reported problems accessing them, leading to feelings of frustration and anger (48).…”
Section: Accessmentioning
confidence: 99%
“…Bariatric surgery results in sustained weight loss and reduced risk of comorbidities (1,2). However, some patients may rely solely on the surgical procedure with the belief that surgery will bring about the behavioral changes that are necessary to lower body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term studies have implied that the level of dietary adherence within the first year after the surgery may play an important role in achieving and maintaining the expected weight loss (2,9). For example, Sarwer et al (10) showed that selfreported ratings of overall adherence to nutritional guidelines at 20 wk after bariatric surgery predicted weight outcomes at 92 wk.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][9][10][11] However, while results from qualitative and quantitative studies on bariatric surgery may imply or directly point to various support needs of bariatric surgery recipients (e.g. addressing disordered eating behaviours, deficits in nutritional status or challenges in adjusting to post-surgical life [12][13][14][15] ), high-quality research is lacking on the type of support and its characteristics that are valued by recipients of bariatric surgery and how support affects surgical outcomes. 3,11,16 Consequently, this study sought to investigate the support experience and needs of publicly or privately funded LAGB recipients and the impact of support on surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%